Stability Evaluation of Non-ideal Grid-tied Photovoltaic on IEEE-9 Bus System - S. D. Lumina; M. E. S. Mnguni; Y. D. Mfoumboulou (International Journal of Electrical Engineering and Applied Sciences)
The integration of photovoltaic in power systems has proved its capability of being a viable source of power to be considered in grid-tied power systems. However, in some cases various electrical challenges may arise when high photovoltaic power is integrated into power systems at the time the voltage collapse caused by an increase in the load consumption. In case of non-ideal grid-tied photovoltaic due to inappropriate or absence of control strategies to regulate the power dispatch between the microgrid and the grid, the photovoltaic power may negatively further affect the grid voltage stability instead of restoring it to the stability level of the electrical grid. This paper investigates the challenge of solar power integration in the grid by demonstrating that due to its randomness and intermittent nature, the photovoltaic power is likely to be associated with voltage disturbance and low power quality that occurs on the electrical grid. Data from simulation of a non-ideal grid-tied photovoltaic are collected to demonstrate the characteristics and negative effects of high photovoltaic integration on the IEEE-9 bus system.